Evolution of sectoral emissions and contributions to mortality from particulate matter exposure in the Asia-Pacific region between 2010 and 2015. (1st November 2019) - Dasadhikari, Kingshuk; Eastham, Sebastian D.; Allroggen, Florian; Speth, Raymond L.; Barrett, Steven R.H.
Abstract: Anthropogenic emissions in the Asia-Pacific region have changed rapidly in recent years due to increasing industrialization and mobility, as well as the implementation of emission abatement controls. These changes are likely to have affected the region's burden of premature mortalities associated with exposure to fine particulate matter (PM2.5 ). However, the contribution of each sector and effectiveness of different policy measures has not yet been quantified. As such, this study estimates changes in regional anthropogenic emissions by sector between 2010 and 2015. These changes are combined with an existing high-resolution emissions inventory to estimate emissions for the year 2015. Using a chemistry-transport model, we then estimate (i) the total contribution of each sector to premature mortality in 2015; and (ii) the effects of changes in each sector's contribution to total PM2.5 -driven premature mortalities between 2010 and 2015. We estimate that globally, 2, 030, 000 (95% CI: 1, 770, 000 to 2, 280, 000) PM2.5 -driven premature mortalities are attributable to anthropogenic emissions in 2015 in Asia-Pacific with the top three sources being the agricultural, industrial, and residential sectors. Between 2010 and 2015, excluding the effects of changes in population distribution or other social factors, sustained growth in economic activity led to an estimated 99, 000 (95% CI: 81, 000 to 130, 000) additional premature mortalities annually, primarily across India, Indonesia, and Bangladesh. Simultaneously, changes such as electrification of railroads and newly-introduced abatement measures, e.g. China's Action Plan on the Prevention and Control of Air Pollution, region-wide adoption of Euro IV/V/VI-compliant road vehicles, and implementation of fuel quality standards, resulted in an estimated total reduction of 76, 000 (95% CI: 65, 000 to 100, 000) annual premature mortalities, primarily across East Asia, including China and Japan. These opposing drivers add to a net change of an additional 22, 000 (95% CI: 12, 000 to 33, 000) PM2.5 -driven annual premature mortalities between 2010 and 2015 associated with anthropogenic combustion emissions in Asia-Pacific. Highlights: An estimated two million early deaths resulted from exposure to fine particulate matter from Asia-Pacific emissions in 2015. Regional agricultural, industrial, and residential emissions were the top drivers. Simulations show 76, 000 fewer early deaths in East Asia in 2015 than 2010 due to abatement measures. Similarly 99, 000 more early deaths estimated in South and Southeast Asia in 2015 than 2010. Increased early deaths driven by activity growth in energy, industrial sectors.